2017
DOI: 10.3390/su9111976
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the “Forgone” ESVs for Small-Scale Gold Mining Using Historical Image Data

Abstract: Ghana's economic development relies largely on the mining industry, but the ecological cost is very high, particularly for the small-scale sector. To ascertain and give an account of the ecological pressures from the small-scale gold mining sector, we quantified and appraised the ecosystems (land cover types) degradation due to mining land use along portions of the renowned Pra River basin of Ghana. The study classified and analysed high-quality Landsat image data to monitor processes and changes in the river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, there is an increasing concern for the health of miners and mining communities related to the mercury exposure, a toxic metal used in small-scale gold mining, and for the ecosystems' degradation due to mining land use [8,9]. Therefore, looking at the total mining costs, such as production costs, economic costs, environmental costs, and social costs, of these two assets or "safe havens", probably a wide spread of Bitcoin could allow us to better address the environmental aspects of sustainability and to have substantially higher savings than gold [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is an increasing concern for the health of miners and mining communities related to the mercury exposure, a toxic metal used in small-scale gold mining, and for the ecosystems' degradation due to mining land use [8,9]. Therefore, looking at the total mining costs, such as production costs, economic costs, environmental costs, and social costs, of these two assets or "safe havens", probably a wide spread of Bitcoin could allow us to better address the environmental aspects of sustainability and to have substantially higher savings than gold [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Land use, on the other hand, involves human activities on the ground including farming, mining, commercial and industrial developments etc. Empirical studies by researchers have established many diverse fields of applications of LULC including geology and mining [5,6], hydrology and water catchments [7], agriculture [8], forestry and wildlife [9,10], urban evolution and regional geography [11], climate change and environmental ecology [12]. The traditional urban growth of Nigeria has always merged all infrastructure development together, including transport, without recourse to their differing critical needs and priorities.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use change is both a cause and consequence of many biophysical and socioeconomic changes ( Van and Verburg, 2013). Human land-use activities have a great impact on biodiversity and the ecological environment by changing the ecosystem (Newbold et al, 2015;Asamoah et al, 2017;Tilman, 2017;Zheng et al, 2020). Research by Song et al (2018) showed that 60% of all land change is related to direct human activities and 40% to indirect drivers such as climate change.…”
mentioning
confidence: 99%